Relationship of External Factors Caused Student’s Learning Difficulties and Biology Learning Outcomes in Class XI IPA MAN 3 Padang City - Rusli, Adithia; Gusmaweti, Gusmaweti; Hendri, Wince; Sari, Rona Taula (Yayasan Nurul Yakin Bunga Tanjung, 2023)
This study aims to determine the external factors that cause student learning difficulties and their influence on the biology learning outcomes of class XI IPA MAN 3 Padang City students. In general, students have learning difficulties due to several factors. One of the influencing factors is external factors, where external factors consist of family, school and community factors. These factors are very influential on student learning outcomes. This type of research is descriptive with quantitative research methods. The research was conducted at MAN 3 Padang City. The sample is all students of class XI IPA as many as 33 students. The sampling technique is a random sampling technique. Collecting data using research instruments in the form of a valid questionnaire of 3.38. The results showed that the external factors of students' learning difficulties, family factors, were 2.42, schools were 2.39 and community factors were 1.8. The highest external factor of learning difficulties is the family factor. There is a significant relationship external factors of learning difficulties to learning outcomes on the 0.05 t test. It can be concluded that t table (3,638>2,040), where Hi is accepted, Ho is rejected, meaning that there is a significant relationship between external factors causing learning difficulties and students' biology learning outcomes. So it is expected for teachers and parents to be able to recognize the learning difficulties that students have, so that learning can run smoothly.